A Global Minimum Tax for Large Firms Only: Implications for Tax Competition - Andreas Haufler; Hayato Kato (Center for Economic Studies and ifo Institute (CESifo), 2024)
The Global Minimum Tax (GMT) is applied only to firms above a certain size threshold, permitting countries to set differential tax rates for small and large firms. We analyse tax competition between a tax haven and a non-haven country for heterogeneous multinationals to evaluate the effects of this partial coverage of GMT. We show that the introduction of a moderate GMT increases tax revenues in both the haven and the non-haven countries. Gradual increases in the GMT rate, however, induce the haven to set a discriminatory, lower tax rate on small multinationals, causing revenues in the non-haven country to decline at the switch of regimes. We also discuss the quantitative effects of introducing GMT in a calibrated version of our model.
Keywords: F23; H25; H87; 330; multinational firms; tax avoidance; Global Minimum Tax; profit shifting; tax competition